Upaya Peningkatan Hasil Belajar Siswa pada Materi Operasi Hitung Pecahan Desimal Menggunakan Alat Peraga di Kelas VA SD Negeri 29 Banda Aceh - Monawati Monawati; Fauzi Fauzi; Rosma Elly; Suci Fitriani (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2021)
Mathematics is concerned with abstract ideas and concepts arranged hierarchically and deductive reasoning. In this study, researchers used teaching aids to improve student learning outcomes in mathematics in the decimal fraction count operations material. The props used are Block Dienes, place value cards, and abacus. The formulation of the problem in this study is "Can the use of teaching aids improve student learning outcomes in the material of the operation of counting decimal fractions in the VA class of SD Negeri 29 Banda Aceh?". Classroom Action Research uses a research design model of Kemmis and M. Taggart with 2 cycles. Data collection techniques are observation and tests. The results of the study in the first cycle of the average student learning outcomes were 89 with a percentage of 88.77% learning completeness, but students who had not achieved learning success were 11.23% of the percentage of classical learning completeness ≥ 85% and individual KKM ≥ 71. achieve mastery learning that is with an average of 98.14 with a percentage of 98.14%. Based on the discussion above shows that efforts to improve learning outcomes in the operation material of counting decimal fractions using teaching aids in VA class SDN 29 Banda Aceh can be increased. This is evidenced by the comparison of the average value on the initial test before using props, namely 40 to 98.14 after using props.